The first successful Hungarian experiment of human scent identification: The first successful detection of human fragrances for forensic purposes (Academic Journal of Internal Affairs, 2015)
The authors provide an overview of the first successful identification of human scent molecules on fixed fabrics in Hungary.
Keywords: human scent molecules; identification; opportunities